Profitability Factors Using the Loans to Deposits Ratio as a Moderating Variable - Jabida Latuamury; Pandu Adi Cakranegara; Ribka Sari Butar- butar; Samuel PD Anantadjaya (Program Pascasarjana STIE Amkop Makassar, 2023)
The establishment of a banking company can benefit the economy and the welfare of the people. Banking institutions lend money to the public in order to keep the economy running smoothly. Banks' primary goal is to increase profits or profitability, which is measured by the value of Return on Assets (ROA). Several factors, including non-performing loans (NPLs) and capital adequacy, can have an impact on profitability (CAR). The goal of this study is to determine the impact of NPLs and CARs on profitability (ROA) using the Loan to Deposit Ratio (LDR) as a moderating variable. Financial statements of publicly listed companies (Tbk) of public and government private banks registered with the Financial Services Authority serve as secondary research data (OJK). Keywoard : Profitability, Loans to Deposits Ratio (LDR), Moderating Variable